Properties of feline leukemia virus. III. Analysis of the RNA. - Brian, D A (1975)
The kinetics of virus labeling was used to study the maturation of viral RNA in the Rickard strain of feline leukemia virus. Viral RNA labeled over differing intervals was characterized by gel electrophoresis and velocity sedimentation in sucrose gradients made up in aqueous buffer and 99% dimethyl sulfoxide. Labeled virus was found within 30 min after adding radioactive uridine to the cells and production of labeled virus reached a maximum at 4 to 5 h after pulse labeling. Native RNA from feline leukemia virus resolved into three size classes when analyzed by electrophoresis on 2.0% polyacrylamide-0.5% agarose gels: a 6.2 x 10(6) to 7.1 x 10(6) mol wt (50 to 60S) class, an 8.7 x 10(4) mol wt (approximately 8S) class, and a 2.5 x 10(4) mol wt (4 to 5S) class. From two experiments during which RNA degradation appeared minimal, these made up to 57 to 76%, 2 to 5%, and 6 to 12%, respectively, of the total RNA. The 8S RNA in feline leukemia virus has not previously been reported. The 50 to 60S RNA from virus harvested after 4 h of labeling electrophoretically migrated faster and sedimented more slowly in sucrose gradients than did the same RNA species harvested after 20 h of labeling. This argues for an intravirion modification of the high-molecular-weight RNA. The large subunits of denatured viral RNA from both 4- and 20-h labeled-viral RNA electrophoretically migrated with an estimated molecular weight of 3.2 x 10(6) but sedimented with 28S ribosomal RNA (1.8 X 10(6) mol wt) when analyzed by velocity sedimentation through 99% dimethyl sulfoxide.